TINJAUAN HUKUM PENETAPAN ZONASI TERHADAPAT MASYARAKAT NELAYAN BERDASARKAN PASAL 23 UNDANG-UNDANG NOMOR 5 TAHUN 1990 TENTANG KONSERVASI SUMBERDAYA ALAM HAYATI DAN EKOSISTEM - Haniru, Laode (Jurnal Hukum Volkgeist, 2017)
Wakatobi National Park (TNW) is managed by the system established based on the decision of the diirektur-General of forest protection and nature conservation (PHKA) number SK. 149/IV-KK/2007 July 23, 2007 by wakatobi National Park alongside Hall Government wakatobi, aimed at mapping the area and restriction area which can be utilized and that cannot be utilized called zoning. Until now the most dominant issue facing the fishermen who came from the tribe of bajo, is poverty the cause there is no other choice but to continuously exploit sea resources, poverty often becomes complicated because of poor population It is often considered as the cause of damage to the coastal environment, but on the other hand the poor population also will bear the impact of environmental damage. The methods used in this study i.e. by using qualitative descriptive method, namely the description of penganalisaan data obtained from field studies and libraries by way of describing and explaining the reality of objective research obtained from the results of observation and interview approaches as well as describe the behavior of the community until the creation of the law. Research results show that implementation of the truly wakatobi National Park Zoning to protect marine ecosystems, particularly coral reefs exist in the Wakatobi. Sustainability of natural resources tersebutnantinya expect able to prosper fishing communities especially in the villages of Mola Samaturu. Though the National Park Zoning designation wakatibi has yet to get a response is entirely from fishing communities especially villagers Mola Samaturu because masi felt there was some space for a living sea becomes limited by the existence of zoning. Wakatobi national park management in kelolah based on the Zoning system, as for the forms is the core zone, the zone of protection zones, exploiting local marine, public utilization zones, tourism and land zone zone/special.